Case Report: Prolonged Neutropenia in Premature Monoamniotic Twins With SARS-CoV-2 Infection Acquired by Vertical Transmission - Anna S. Scholz; Stephanie Wallwiener; Johannes Pöschl; Navina Kuss (Frontiers Media S.A., 2022)
BackgroundVertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a highly debated topic in the current pandemic situation. Early neonatal SARS-CoV-2 infection is rare and generally mild. Long-term data describing symptoms after COVID-19 in premature neonates is scarce.Case PresentationTwo premature, monoamniotic neonates were born by cesarean section to a mother 5 days after onset of symptomatic COVID-19. On day three of life both neonates developed hyperthermia, respiratory distress, and hematological changes, of which neutropenia persisted for over 40 days. Nasopharyngeal swabs for SARS-CoV-2 turned positive four days after delivery although the neonates were strictly isolated. Both neonates showed nearly identical time courses of ct values.ConclusionOur case report revealed prolonged low absolute neutrophil counts in two preterm neonates with symptomatic SARS-CoV-2 infection that is reasonably assumed to have been transmitted vertically in utero. After preterm delivery to a SARS-CoV-2 positive mother, testing for SARS-CoV-2 infection in neonates is crucial. Both neutropenia and lymphopenia should alert physicians to test for SARS-CoV-2 infection and also to follow the case.